Hayy ibn Yaqzan: Ibn Tufayl's Masterpiece - Halilović Tehran (Kom: Časopis za Religijske Nauke)
Ibn Tufayl, the great Andalusian thinker of the 12th century, is important in the history of Islamic philosophical thought because of his masterpiece Hayy ibn Yaqzan. Ibn Tufayl's novel is one of the most translated texts of Islamic philosophy into Western languages. Hayy ibn Yaqzan is a story about a child born and raised on an island far from civilization and according to many historians of Islamic philosophy, it symbolizes the human soul on its developing spiritual journey towards eternal bliss. Ibn Tufayl's introduction to the book gives a unique insight into the thought background of this philosopher and shows how familiar Ibn Tufayl was with the ideas of prominent Islamic philosophers. The fact that Ibn Tufayl was not a student of any of the four philosophers he names in the introduction - Farabi, Ibn Sina, Ghazali and Ibn Bajja - justifies the choice of the translators of his book to give him the title of self-taught philosopher. Knowing that Hayy ibn Yaqzan is the story of a self-taught man, this nickname can be an additional sign that Ibn Tufayl wrote about himself in the novel. The main motive of Ibn Tufayl's Hayy ibn Yaqzan is the harmony of religion and science, that is, philosophy. Over time, Hayy unravels most of the most significant scientific achievements of Ibn Tufayl's time to finally devote himself to thinking about the origins of being. This thought development, before Absal, a symbol of religious revelation or mystical tradition, comes to the island, Hayy achieves independently without the help of other cognitive beings. Hayy's autodidacticism symbolizes the self-sufficiency of the rational method in dealing with the truth. From Absal, Hayy learns how to speak and learns about religious rituals, which he begins to practice. The pinnacle of Ibn Tufayl's skill in showing the harmony between religion and philosophy is reflected in the fact that Ibn Tufayl writes about philosophical discoveries in the allegorical language of religion.